2019
DOI: 10.1016/j.jvb.2019.103326
|View full text |Cite
|
Sign up to set email alerts
|

Attracting applicants through the organization's social media page: Signaling employer brand personality

Abstract: The purpose of this study is to examine how potential applicants' exposure to an organization's social media page relates to their subsequent organizational attractiveness perceptions and wordof-mouth intentions. Based on signaling theory and the theory of symbolic attraction, we propose that potential applicants rely on perceived communication characteristics of the social media page (social presence and informativeness) as signals of the organization's employer brand personality (warmth and competence), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 68 publications
(121 reference statements)
4
76
0
4
Order By: Relevance
“…The latter, in turn, increased the application intentions of Russian Millennials to participate in selection procedures in FMCG multinationals. These findings correspond with the previous research regarding the relationship between the perceived quality of information from the social media and employer attractiveness (Carpentier, Van Hoye, and Weijters 2019) and subsequent application intentions (Sivertzen, Nilsen, and Olafsen 2013) of young specialists.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The latter, in turn, increased the application intentions of Russian Millennials to participate in selection procedures in FMCG multinationals. These findings correspond with the previous research regarding the relationship between the perceived quality of information from the social media and employer attractiveness (Carpentier, Van Hoye, and Weijters 2019) and subsequent application intentions (Sivertzen, Nilsen, and Olafsen 2013) of young specialists.…”
Section: Discussionsupporting
confidence: 91%
“…Two years later (Carpentier, Van Hoye, and Weijters 2019) conducted the research to examine how potential applicants' exposure to an organization's social media page related to their subsequent organizational attractiveness perceptions and word-of-mouth intentions. Data gathered from the survey among 165 final-year Master's students Business Administration of a Belgian university revealed that the perceived social presence of a social media page was indirectly positively related to attractiveness and word-of-mouth through its positive association with perceived organizational warmth.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, we did not systematically include important employer brand material such as company websites, employer's social media page (Carpentier et al 2019) or company-independent information on social media (e.g., Sivertzen et al 2013) and on platforms for employer evaluation. However, company-independent sources played a role in our empirical study when participants related to information on social media or platforms in the interviews.…”
Section: Study Limitations and Further Researchmentioning
confidence: 99%
“…Such results include, e.g. the employer's brand and related market advantages (Carpentier et al, 2019;Green, 2019;Urbancová & Hudáková, 2017), as well as the achievement of strategic goals of enterprises (Clinton, 2016;Sohel-Uz-Zaman et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%